Plant loading uncertainties and their incorporation in probabilistic creep damage assessments. (November 2020) - Zentuti, N.A.; Booker, J.D.; Bradford, R.A.W.; Truman, C.E.
Abstract: This work presents methodologies for the examination of uncertainties in plant loading conditions for incorporation in probabilistic creep-fatigue (CF) crack initiation assessments. These approaches are based on the use of plant data for transient (TR) as well as steady-operating (SO) conditions, with both potentially having large contributions towards creep-fatigue damage. Conventionally, the stress-states in a boiler plant component are found using thermal and mechanical (elastic) finite element (FE) models. The main inputs to these models are the boiler steam temperatures, while the outputs are the six stress components (SCs) and the metal temperature (MT) at the assessment location(s) of interest. The proposed methodologies were developed based on experience gained from examining a tube-plate (TP) plant component, for which historical data was available. In a probabilistic lifetime assessment, the aim of these approaches is to replace time intensive FE runs with probabilistic alternatives which incorporate the load variabilities of interest. The value of these approaches lies in the avoidance of running FE models for every probabilistic trial (e.g. a Monte-Carlo simulation may require more then 10 5 trials), which may be computationally prohibitive.